Stretch-activated channels in the heart: Contributions to length-dependence and to cardiomyopathy - Ward, Marie-Louise; Williams, Iwan A.; Chu, Yi; Cooper, Patricia J.; Ju, Yue-Kun; Allen, David G. (Progress in biophysics and molecular biology, 2008)
The stretch-induced increase in force production of ventricular muscle is biphasic. An abrupt increase in force coincides with the stretch, which is then followed by a slower response that develops over minutes (the slow force response or SFR). The SFR is accompanied by a slow increase in the magnitude of the intracellular Ca 2+ transient, but the stretch-dependent mechanisms that give rise to this remain controversial. We characterized the SFR using right ventricular trabeculae from mouse hearts. Application of three different blockers of stretch-activated non-selective cation channels (SAC NSC) reduced the magnitude of the SFR 60 s after stretch (400 μM streptomycin: from 86±25% to 38±14%, P<0.01, n=9; 10 μM GdCl 3: from 65±21%, to 12±7%, P<0.01, n=7; 10 μM GsMTx-4 from 122±40% to 15±8%, P<0.05, n=6). Streptomycin also decreased the increase in Ca 2+ transient amplitude 60 s after the stretch from 43.5±12.7% to 5.7±3.5% ( P<0.05, n=4), and reduced the stretch-dependent increase in intracellular Ca 2+ in quiescent muscles when stretched. The transient receptor potential, canonical channels TRPC1 and TRPC6 are mechano-sensitive, non-selective cation channels. They are expressed in mouse ventricular muscle, and could therefore be responsible for stretch-dependent influx of Na + and/or Ca 2+ during the SFR. Expression of TRPC1 was investigated in the mdx heart, a mouse model of Duchenne's muscular dystrophy. Resting Ca 2+ was raised in isolated myocytes from old mdx animals, which was blocked by application of SAC blockers. Expression of TRPC1 was increased in the older mdx animals, which have developed a dilated cardiomyopathy, and might therefore contribute to the dilated cardiomyopathy.